Basal Cell Carcinoma in a Child - Samet Vasfi Kuvat; Zuhal Gücin; Barış Keklik; Gülzade Özyalvaçlı; Karaca Başaran (Journal of Skin Cancer)
Basal cell carcinoma is the most commonly seen nonmelanoma skin cancer which is rarely encountered in the childhood period. An 11-year old child was admitted to our clinic due to an erythematous and a slightly pigmented lesion with a 3×4 cm diameter on his posterior scalp. Macroscopically, the lesion was excised with a 10 mm safety margin. Pathologic examination revealed a basal cell carcinoma. No symptoms or signs of a syndrome were observed both in the patient and his family.